2001
DOI: 10.1128/jb.183.8.2634-2645.2001
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Colonization of Rice by a Diazotrophic Strain of Serratia marcescens

Abstract: Six closely related N 2 -fixing bacterial strains were isolated from surface-sterilized roots and stems of four different rice varieties. The strains were identified as Serratia marcescens by 16S rRNA gene analysis. One strain, IRBG500, chosen for further analysis showed acetylene reduction activity (ARA) only when inoculated into media containing low levels of fixed nitrogen (yeast extract). Diazotrophy of IRBG500 was confirmed by measurement of 15 N 2 incorporation and by sequence analysis of the PCR-amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
189
2
19

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(220 citation statements)
references
References 72 publications
10
189
2
19
Order By: Relevance
“…Surface sterilisation is insufficient evidence to ascribe an endophytic fungal location, and microscopy is considered as the only direct evidence (James 2000; Gyaneshwar et al 2001) to ascribe the location. According to Kuldau and Yates (2000), light and electron microscopy can reveal the precise internal locations of endophytic fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Surface sterilisation is insufficient evidence to ascribe an endophytic fungal location, and microscopy is considered as the only direct evidence (James 2000; Gyaneshwar et al 2001) to ascribe the location. According to Kuldau and Yates (2000), light and electron microscopy can reveal the precise internal locations of endophytic fungi.…”
Section: Introductionmentioning
confidence: 99%
“…They improve plant growth via nitrogen fixation, suppression of plant pathogens and production of phytohormones and enzymes involved in the metabolism of growth regulators such as ethylene, 1-aminocyclopropane 1-carboxylic acid (ACC), auxins and indole-3-acetic acid (IAA) (Gyaneshwar et al, 2001; Kämpfer et al, 2005;Taghavi et al, 2009).…”
mentioning
confidence: 99%
“…The final pH was adjusted to 7.0 by KOH. The NfM was modified by adding 0.02 g yeast extract (NfM+Y), as it has already been reported that a trace amount of fixed nitrogen is required for the isolation of most diazotrophs from the rhizosphere of rice (Gyaneshwar et al, 2001). The samples were incubated at 28 u C for 4-5 days.…”
mentioning
confidence: 99%